Geological and biotic context of the Plio-Pleistocene evolution of the Caucasus-Caspian Region (Akchagylian transgression) - Trifonov, Vladimir G.; Tesakov, Alexey S.; Simakova, Alexandra N.; Gaydalenok, Olga V.; Frolov, Pavel D.; Bylinskaya, Marina E.; Hessami, Khaled (Pergamon-Elsevier Science Ltd, 2024)
We discuss geological and biotic aspects of the extensive Akchagylian transgression that occurred in the Caspian region of Eurasia near the Plio-Pleistocene transition, in Piacenzian and Gelasian. It is shown that the onset of the Akchagylian marine sedimentation in Western Turkmenistan (ca. 3.2 Ma) preceded that in the Kura Basin (ca. 3.0 Ma). The position of the upper boundary of the Akchagylian remains uncertain (ca. 2.1 or 1.8 Ma). The analyzed biotic content of the Akchagylian includes molluscs, microfossils (pollen, dinocysts, foraminifers), and mammals. It is noted that specific forms of the Akchagylian aquatic biota co-occur with microfossils that clearly indicate a connection with the World Ocean or related seas. The palynology of the Akchagylian time signals a directed cooling in the Pliocene and Early Pleistocene with several warm and humid epochs. The Akchagylian transgression was preceded by a change of a structural-sedimentary pattern of the region. In the latest Miocene and Early Pliocene, a pre-existed longitudinal tectonic zonation of the Caucasian-Caspian segment of the Paratethys gradually changed into clearly transverse tectonic zonation. The latter was manifested in the tectonic uplift of the Greater Caucasus, its northern piedmonts and the Lesser Caucasus, and in the subsidence of the western parts of the South and Middle Caspian basins. The interplay of longitudinal and transverse tectonic features shaped the configuration of the Akchagylian brackish-water basin and controlled thickness of its deposits. It was the transverse zonation that dominated in the thickness pattern. The increasing role of the transverse zonation in the post-Akchagylian time is manifested in the magnitudes and rates of the Quaternary tectonic uplift. These parameters were calculated based on current heights of the top of the Akchagylian marine deposits in different parts of the basin. The highest magnitudes of uplift are found in the Eastern Caucasus (up to 1980 m on the NE slope and about 2500 m in the axial part) and in the west of the Lesser Caucasus in eastern Turkey (up to 1750 m). The maximum level of the Akchagylian transgression is estimated at 40-50 m above the present level of the World Ocean. We show a low probability of connection of the Akchagylian basin with the Mediterranean Sea or the Persian Gulf, and a high probability of its connection with the Arctic Ocean through the northern tributaries of the Kama River and the Pechora Basin in the NE of East European Plain.
Keywords: Akchagylian; Plio-Pleistocene; Stratigraphy; Tectonics; Biota; Paleogeography